Social Capital and Social Well-Being: A Systematic Review - Iqbal, Mian Muhammad Ahamd; Hussain, Ghazanafar; Siddique, Kashif (Pakistan Journal of Humanities and Social Sciences, 2022)
Social capital and social well-being are important social assets that play a vital role in any society's social and economic development. However, the major objectives of this systematic review are; to conceptualize social capital and social well-being and to identify if there is any relationship between these attributes. For this purpose, 49 studies were summarized from the database. The findings revealed that social capital is a multidimensional concept covering three subtypes: bonding, bridging, and linking capitals. These types are based on trust and reciprocity. Similarly, social well-being is also a multilevel construct that covers social integration, social acceptance, social contribution, social coherence, and social actualization. Literature depicts a meaningful link between social capital and social well-being. However, only five studies in prior literature focused on the relationship between social capital and social well-being. Of these studies, only one study found a relationship between various types of social capital with social well-being. Future researchers should comprehensively integrate these constructs in their theoretical frameworks to fully operationalise the relationship between social capital and social well-being.